Exploring heterogeneity in meta-analyses using summary and individual patient data methodologies from stroke trials - Leonardi-Bee, Jo (2005)
Until recently, meta-analyses have usually been performed based on summary data methods. Individual patient data methods are becoming more popular, but the advantages of using these methods have not been fully investigated with regards to assessing and exploring heterogeneity.